English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2 answers

When x=-2 the denominator will equal zero. To prevent a vertical asymptote, 3(-2)+p must also be zero: therefore, p=6.

2007-01-23 03:18:12 · answer #1 · answered by bruinfan 7 · 0 0

you can write the denominator as (x+2)*(x^2-2x+4) becaus e -2 is a root.
So it aloso should be a root f the numerator
so if x=-2 3(-2)+p=0 ===> p= 6. and you can simplify
There are NO other roots in the denominator

g(x) =3/(x^2-2x+4)

2007-01-23 11:54:15 · answer #2 · answered by santmann2002 7 · 0 0

fedest.com, questions and answers